A desjudicialização da execução individual no processo coletivo: uma proposta para conferir efetividade à tutela coletiva - Silva, Geocarlos Augusto Cavalcante da (2019)
This paper defends the thesis that the judgment execution by the individual benefited by a class action can be obtained in a more effective and efficient way with the accomplishment of the liquidation and the satisfaction of judgment administratively and at the expense of the defendant. The thesis is based on two premises: a) the National Council of Justice's observation that the cognizance stage, although more complex, is faster compared to the phase of enforcement of the decision; and b) when there is no real conflict between the parties, the request provided for in article 523 of the Code of Civil Procedure represents a mere bureaucracy. The thesis has at least two advantages: a) preservation of the resources of the Judiciary for those situations in which the conflict is actually effective (deliberate and unjustifiable resistance to enforcement of judgment); and b) the judgment execution in the way that proposal may represent less costs to the beneficiary, since the latter will not be required to collect costs or even hire lawyers. For the success of this thesis, it is necessary not to have a generic judgment, that is, without defining the necessary requirements for the creditor and the debtor to objectively understand the legal and economic sense of the judicial decision; and determination in the judgment of the cognizance stage of sanctions for whom, creditor or debtor, present unjustifiable obstacles to the material realization of the right. The thesis is in conformity with the constitutional text because it has the objective of realizing the fundamental right to the reasonable duration of the process (Article 5º, LXXVIII, of the Federal Constitution)